Effect of Culture Density on Growth, Digestive Enzymes, and Intestinal Flora of Net-Cage Culture of Sea Cucumber (Apostichopus japonicus) Under Feeding Mode - Yiming SONG; Jianlong GE; Meijie LIAO; Bin LI; Xiaojun RONG; Yingeng WANG; Jinjin WANG; Limei CHEN (Progress in Fishery Sciences)
The shallow-sea net-cage culture of sea cucumber (Apostichopus japonicus) has been developing rapidly in recent years, and the culture mode of feeding formula feed has been accepted by farmers. However, the optimal culture density under the feeding mode is still unknown. To evaluate the influence of culture density on the shallow sea net-cage culture of sea cucumber under a feeding mode, this study examined the growth, digestive enzymes, and gut bacterial community structure of sea cucumber at different culture densities. The culture density was set to 10 kg/cage, 20 kg/cage and 30 kg/cage, marked as F10, F20 and F30, respectively. Sea cucumber seedlings with an initial body weight of (75.11±2.99) g were randomly assigned into 9 cages (3 replicates of each density level) according to the density settings. The net cage is cuboidal and its length, width and height were 4 m, 4 m, and 3 m, respectively. After a 42-day experimental period, the total weight of sea cucumber in each cage was weighted and 20~30 individuals in each cage were randomly sampled for individual weight and body wall weight. Then, intestines from 3 individuals were sampled and preserved at –80 ℃ freezer. Digestive enzyme (Trypsin, Amylase, and Lipase) activities were determined spectrophotometrically using enzyme activity assay kits (Nanjing Jiancheng Bioengineering Institute, China) following the manufacturer's instructions. Gut microbial DNA was extracted, and the V3~V4 region of the prokaryotic ribosomal RNA gene (16S rDNA) was amplified and sequenced on an Illumina Novaseq platform. Sequence data were then analyzed on the platform BMKCloud (www.biocloud.net). The results showed that as culture density increased, the weight gain rate of sea cucumbers in net-cage culture significantly decreased, and both the F20 and F30 groups had significantly lower weight gain rates compared to the F10 group (P < 0.05). In addition, increasing culture density resulted in a significant increase in net production and body wall production rates, although none of the differences were significant (P < 0.05). The feed conversion ratio of the F10 group was the lowest and not significantly different from that of the F20 group, but significantly lower than that of the F30 group (P < 0.05). The enzyme activities of all three digestive enzymes showed a decreasing trend with the culture density increase. The digestive enzyme activity of F30 was significantly lower than that of F10 and F20 (P < 0.05). The similarity of the bacterial community structure between the F10 group and F20 group was relatively high. The ACE index of F10 group was significantly lower than that of the F20 group (P < 0.05), while the Chao1 index, Shannon's index and Simpson's index showed no significant difference from that of the F20 group (P > 0.05). All the microbial diversity indices of the F30 group were significantly lower than those of the other density groups (P < 0.05). The relative abundance of dominant organisms varied with culture density. The relative abundance of Firmicutes and Actinobacteria tended to decrease with increasing density, while the opposite was true for Bacteroidota and Proteobacteria. The relative abundance of Actinobacteria in group F10 was significantly higher than that of group F30 (P < 0.05). The relative abundance of Lachnospiraceae, Bifidobacteria and Streptococcus was significantly higher in group F10 than in groups F20 and F30 (P < 0.05), and the relative abundance of Oscillospiraceae and Rikenellaceae was significantly higher in the F20 group than in the F10 and F30 groups (P < 0.05). LEfSe analysis showed that F10, F20, and F30 were mainly significantly enriched in Streptococcus, Ruminococcus UCG_005 and Alkanindiges, respectively. Pearson's correlation analysis showed that three gut bacteria genera were significantly positively correlated with digestive enzyme activities, including Streptococcus, unclassified_ Muribaculaceae and UCG_005. According to the benefit estimation, there was little difference in culture benefit between the F20 and F30 groups, both of which were significantly higher than the F10 group. The results indicate that higher culture densities can improve the net-cage culture production of sea cucumber, thus increasing the overall benefit. However, too high culture density could negatively affect the growth, digestive enzymes, and the gut microbial balance of the sea cucumber. Therefore, to improve the overall benefit, it is better to increase the culture density to 20 kg/cage in the current small net-cage feeding mode. These results provide references for the scientific culture of sea cucumbers in shallow-sea net-cage systems, leading to improvements in both quality and culture efficiency.